The influence of rainfall on the mechanics of soil erosion : with particular reference to Southern Rhodesia. - Hudson, Norman Webster (Department of Civil Engineering, 2015)
Today soil erosion is almost universally recognised as a serious threat to man's well-being, if not to his very existence, and this is shown by the fact that most Governments outside Europe give active support to programmes of soil conservation. But it is relevant, before making any assessment of present knowledge of erosion, to consider the development of this science which was almost unknown eighty years ago, and now enjoys world wide attention.